Middle-aged and older people's preference for medical-elderly care integrated institutions in China: a discrete choice experiment study - Mao-min Jiang; Mei-fang Xiao; Jia-wen Zhang; Mei-fang Yang (BMC, 2024)
Abstract Background With the continuing impact of the aging population, medical-elderly care integrated institutions, as a way to bear the pressure of medical and elderly care, effectively ensure the quality of life of the elderly in their later years. Objectives To explore the preferences of medical-elderly care integrated institutions among Chinese middle-aged and older people and to provide a reference for establishing elderly-oriented development of medical-elderly care integrated institutions. Methods In this study, a discrete choice experiment (DCE) was used to investigate the preferences of people aged 45 years and older in medical-elderly care integrated institutions in China from October 20, 2022, to November 10, 2022. A mixed logit regression model was used to analyze the DCE data. Participants' willingness to pay for each attribute was also calculated. Results Data from 420 participants who provided valid responses were included in the analysis. In terms of the choice preference, moderate service quality (vs. poor service quality: β = 1.707, p < 0.001, 95% CI 1.343 ~ 2.071) and high medical technology level (vs. low medical technology level: β = 1.535, p < 0.001, 95% CI 1.240 ~ 1.830) were the most important attributes to middle-aged and older people, followed by monthly cost, environmental facilities, the convenience of transportation, and entertainment activities. Regarding the willingness to pay, participants were more willing to pay for service quality and medical technology level than for other attributes. They were willing to pay $3156 and $2838 more for "poor service quality" and "low medical technology level," respectively, to receive "moderate service quality " (p = 0.007, 95% CI 963 ~ 5349) and "high medical technology level" (p = 0.005, 95% CI 852 ~ 4824). Conclusions The state should attach great importance to the development of medical-elderly care integrated services industry, actively optimize the model of the medical-elderly care integrated service, improve the facilities, and create a healthy environment. At the same time, give full play to the role of medical insurance, long-term care insurance, and commercial insurance, so as to improve the comprehensive quality of life of the elderly. Public contribution The design of the experimental selection was guided by 10 experts in the field, 5 Chinese government officials, and interviews and focus group discussions, without whose participation this study would not have been possible.